774. Extrapulmonary Tuberculosis: Impact of Early Diagnosis and Treatment on Mortality. (26th November 2018) - Walayat, Saqib; Awwal, Talha; Ren, Jimna; Farrell, John
Abstract: Background: Pakistan has a high burden of endemic Mycobacterium tuberculos is complex (MTC) disease. Extrapulmonary tuberculosis (EPT) is defined as MTC infection involving any part of the body other than the lung. Extrapulmonary tuberculosis (EPT) is seen 20% of MTC infection in Pakistan, diagnosis is often delayed, and timeliness of initiation of treatment is extremely varied. We conducted a retrospective review of all cases of EPT presenting to a large public hospital in Islamabad, Pakistan to identify the role of early diagnosis and clinical treatment on patients with extra pulmonary tuberculosis. Methods: Retrospective review of EPT diagnosed at Pakistan Institute of Medical Sciences (PIMS), Islamabad, Pakistan. All cases diagnosed and treated as EPT from January to June 2016 were included. Demographic, clinical and laboratory data were extracted from PIMS Medical records and TB01 cards from the National TB Control Program Pakistan. All patients were contacted to determine outcome status. Study was approved from National TB control Program. Results: Two hundred seventy-five patients were identified who received a diagnosis of EPT. Mean age was 34.4 years; ratio of men to woman was 1.3:1. Pleural tuberculosis was the most common site involved (28.7%). The next most frequent site involved was lymphatic disease (20.3%). 47.6 percent of patients (113/275) were diagnosed by clinical criteria alone (i.e., symptoms and radiographic imaging). There were only three cases of culture confirmed EPT in the cohort. The overall cure rate was 82.9%. There was no difference of cure rates between the cure rates of males and females. Diagnosis based on clinical criteria was associated with significantly higher cure rate (87.6% vs. 79.6%, P = 0.038) and lower mortality (5.3% vs. 9.3%, P = 0.041) compared with laboratory-based diagnosis (5.3% vs. 9.3%, respectively). Improved outcomes and mortality benefit was seen in patients who were treated based on clinical criteria as compared with those in whom treatment was delayed due to biochemical confirmation (Odds ratio 0.28, 95% CI: 0.086–0.95). Sixteen cases were lost to follow-up. Conclusion: Early initiation of treatment based on clinical criteria was associated with lower mortality and overall outcome benefit in our study cohort. However, further larger studies of patients with EPT are required to validate our observations. Disclosures: All authors: No reported disclosures.